Identification of target genes of the homeotic gene Antennapedia by enhancer detection. - Wagner-Bernholz, J.T.; Wilson, C.; Gibson, G.; Schuh, R.; Gehring, W.J. (Genes & Development, 1991)
Localized expression of the homeotic gene Antennapedia (Antp) in Drosophila melanogaster is required for normal development of the thoracic segments. When the Antp gene is expressed ectopically in the larval primordium of the antenna, the antennal imaginal disc, the developmental fate of the disc is switched and the adult antenna is transformed to a mesothoracic leg. We screened approximately 550 different fly strains carrying single copies of an enhancer-detector transposon to identify regulatory elements and corresponding genes that are either activated or repressed in antennal discs in response to this transformation. Several regulatory elements that are either direct or indirect targets of Antp were found. One transposant that expresses the reporter gene (lacZ) in the antennal disc, but not in the leg disc, was studied in more detail. The enhancer detector in this strain is located near a similarly regulated gene at the spalt (sal) locus, which encodes a homeotic function involved in embryonic head and tail development. The expression of this newly discovered gene, spalt major (salm) is strongly repressed in gain-of-function mutants that express Antp in the antennal disc. Recessive loss-of-function mutations (Antp-) have the opposite developmental effect; they cause the differentiation of antennal structures in the second leg disc. Accordingly, salm is derepressed in clones of homozygous Antp- cells. Therefore, we conclude that Antp negatively regulates salm. The time course of the interaction and reporter gene fusion experiments suggests (but does not prove) a direct interaction between Antp and cis-regulatory elements of salm. Our analysis of several enhancer-detector strains suggests that the basic patterning information in the antennal and leg imaginal discs is very similar.